2007
DOI: 10.1159/000107512
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Promotes Endothelial Dysfunction by Stimulating Multiple Sources of Superoxide Anion Radical Production and Decreasing Nitric Oxide Bioavailability

Abstract: Hydrogen peroxide (H2O2) is an oxidant implicated in cell signalling and various pathologies, yet relatively little is known about its impact on endothelial cell function. Herein we studied the functional and biochemical changes in aortic vessels and cultured porcine aortic endothelial cells (PAEC) exposed to H2O2. Exposure of aortic rings to 25 or 50 µM, but not 10 µM, H2O2 for 60 min prior to constriction significantly decreased subsequent rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 60 publications
2
40
0
Order By: Relevance
“…4), suggesting that oxidative stress is a necessary cue in ferritin H activation by rotenone. Several recent studies have reported that in some conditions, especially hypoxia, rotenone reduces mitochondrial ROS generation [34][35][36]. To date there is no clear consensus about the effect of rotenone on mitochondrial ROS generation under various conditions; however, such contradictory reports support the need for further investigation into the intricacies of mechanisms of mitochondrial ROS generation and suppression.…”
Section: Discussionmentioning
confidence: 99%
“…4), suggesting that oxidative stress is a necessary cue in ferritin H activation by rotenone. Several recent studies have reported that in some conditions, especially hypoxia, rotenone reduces mitochondrial ROS generation [34][35][36]. To date there is no clear consensus about the effect of rotenone on mitochondrial ROS generation under various conditions; however, such contradictory reports support the need for further investigation into the intricacies of mechanisms of mitochondrial ROS generation and suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various biological effects attributed to ROS, vascular endothelial dysfunction has consistently been noted, irrespective of the preparations used. 2,18) In addition, ROS generated by the XϩXOD system caused contraction of rat pulmonary artery 19) and canine basilar artery, 20) whereas it relaxed canine coronary artery, 21) implying the existence of species or tissue differences in response to ROS. Furthermore, the responses of arteries to ROS are well-known to be influenced by the presence of endothelium.…”
mentioning
confidence: 99%
“…It is known that under diabetic conditions there are increased oxidative stress levels [68]. Increased ROS prompts the EPCs to produce pathologic cytokines such as monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor-α (TNF-α), NF-κB, interleukin-8 (IL-8), elevated levels of iNOS, and decreased eNOS.…”
Section: Diabetic Nephropathy and Vascular Endothelial Dysfunctionmentioning
confidence: 99%
“…In disease states such as diabetes, vascular production of reactive oxygen metabolites can increase substantially [68]. Increased production of the superoxide anion can lead to decreased tissue bioavailability of nitric oxide (NO) via a facile radical/radical reaction that occurs more rapidly than the reaction of with superoxide dismutase (SOD) [71].…”
Section: Diabetic Nephropathy and Vascular Endothelial Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation